The Role Of Technology On Students Assignment Completion: Study Conducted At Muhammadiyah Manadouniversity - Mutiara Dyina Sari Laya (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Technology can be explain as a scince to produces the art of craft or skill. Most people in this world have a good grip with technology. The aims of this reasearch is to examine the effectiveness of technology on to help students assignment completion in English subject Muhammadiyah Manado Universities. This research acumulate the data by semi-structured interview is finding qualitative research, this study employed a blend of closed- and open-ended questions, often accompanied by follow-up why or how questions. About one hour is considered a reasonable maximum length for SSI. The target population is 10 technology user students at Muhammadiyah Manadi Universities. This research concluded the technology is effectifly be participation tool in the classroom with teachers who help to the success of the implementation of technology in the class,the students have positive response is to be a conclusion toward the use of to learn. According to the students it can minimize the mistakes in doing the task, enable them to finish the tasks in shorter time and increase their self confidence in expressing the ideas.